APPLICATION OF ONLINE SINGLE SUBMISSION (OSS) INNOVATION IN THE INTEGRATED INVESTMENT AND SERVICE OF BULUNGAN DISTRICT - Imam Muazansyah (DIA: Jurnal Administrasi Publik, 2020)
The application of one-stop integrated admission services at the Office of Investment and One-stop Integrated Services (Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu/DPMTSP) of the Bulungan District which has the aim of making it easy for the public or business actors to manage their licenses and accelerate the process of admission issuance services, just by visiting one agency. The research methods used are descriptive qualitative and the source of the data used are primary data sources in the form of in-depth interviews and field observations as well as secondary data sources of notes, reports, regulations obtained in the field. Methods of data collection using semi-structured interviews, observations, and documentation review. Data analysis techniques using data reduction, data presentation, and conclusion drawing. The validity of the data used triangulation namely time triangulation, source triangulation, and technical triangulation. The results showed that the application of public service innovation in the form of OSS services with research dimensions, including ICT connectivity, ICT use and integration, training, Human Resources capacity, local policies and regulations, infrastructure, security, access, and application services.